Potensi Ekstrak Biji Coklat (Theobroma cacao Linn) sebagai Inhibitor Tirosinase untuk Produk Pencerah Kulit - Kurniasari, Aprilia; Anwar, Effionora; Djajadisastra, Joshita (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2018)
Hyperpigmentation is a condition of excessive skin pigments production. The skin colour is strongly influenced by the presence of melanin that marked by the melanin tyrosinase enzyme activity. Cocoa (Theobroma cacao Linn) is one of the ingredients which are rich in flavonoids include polyphenolic compounds that used as antioxidants and a tyrosinase inhibitor. The aim of this study is to examine the potential of the cocoa bean extract as a tyrosinase inhibitor for skin lightening active ingredients. The method of the study was experimental laboratories, among others: total flavonoid and tyrosinase inhibitory activity assay. The result of this research was ethanol extract of cocoa had tyrosinase inhibitor activity. The inhibitory activity could be seen from the IC50 for monophenolase activity were 352.05 μg mL-1 and for diphenolase activity 836.20 μg mL-1 respectively. This value is greater than kojic acid, for monophenolation was 2.38 μg mL-1 and diphenolation was 10.74 μg mL-1. The total flavonoids content was 0.05% w/w so that the ethanol extract of the cocoa bean is a natural product that potential to be used in the formulation of skin lightening cream in the pharmaceutical sciences.